Optimized feedforward control of propofol for induction of hypnosis in general anesthesia. (April 2021) - Schiavo, Michele; Consolini, Luca; Laurini, Mattia; Latronico, Nicola; Paltenghi, Massimiliano; Visioli, Antonio
Highlights: Induction phase of general anesthesia is considered. An optimization strategy is employed to determine of the initial propofol bolus. The optimized bolus minimizes the time-to-target. It is used as a feedforward control action with the bispectral index as the controlled variable. Abstract: Objective: We propose the use of an optimization strategy for the determination of the initial propofol bolus for the induction phase of general anesthesia. Methods: The optimized bolus minimizes the time-to-target and it is used as a feedforward action together with a specifically tuned PID feedback control system where the bispectral index is the controlled variable. Results: A Monte Carlo method is used to verify the effectiveness of the proposed technique. Both intra-patient and inter-patient variability has been considered. A comparison with a control scheme based on a feedback PID controller only shows that the use of an optimized feedforward action allows an average reduction of the time-to-target of more than 25%, with an acceptable increment of the undershoot, which always remains above the BIS level of 30. Conclusions: The use of an optimized bolus of propofol as a feedforward action in a fully automatic control system for the induction phase of anesthesia allows the anesthesiologist to reduce the transient time to obtain the required level of depth-of-hypnosis, without affecting the safety of the patient.